OP0268 Anti-Citrullinated Protein Antibody (ACPA) Status in the General Population and as a Predictor of Future Inflammatory Polyarthritis: The EPIC-2-Noar Study. (9th June 2015) - Verstappen, S.M.; Sergeant, J.C.; Luben, R.N.; Bhaniani, A.; Anuj, S.; MacGregor, A.; Wareham, N.; Symmons, D.P.; Khaw, K.T.; Bruce, I.N.
Abstract : Background: Anti-citrullinated protein antibody (ACPA) immune response occurs several years prior to the diagnosis of rheumatoid arthritis (RA). However, limited data are available on ACPA status in the general population compared to those who develop RA or inflammatory polyarthritis (IP) in the future. Objectives: The aim of this study was to examine ACPA status in the general population and in patients developing IP/RA. Methods: ACPA was measured by ELISA (Euro-Diagnostica) in stored serum samples collected at baseline in people participating in the European Prospective Investigation of Cancer in Norfolk, (EPIC-Norfolk), a prospective population-based study in the UK. In addition, data on ACPA status (positive >25 U/ml) age, gender, socio-economic status (i.e. manual/unskilled worker, manager/skilled non-manual worker, professional), smoking status (i.e. never, former, current) were also collected at inclusion. Individuals who subsequently developed IP/RA were identified by linkage with the Norfolk Arthritis Register (NOAR), a primary-care based cohort with an overlapping catchment area in the UK. Logistic regression analyses were used to assess the association between demographic characteristics and ACPA positivity in the general population. Cox regression analyses were performed to assess the association between ACPA and the development of IP, adjusting for age and gender. Patients with a symptom onset prior to inclusion in EPIC-Norfolk were excluded from the Cox regression analysis (N=104). In addition, the interaction between ACPA and smoking was tested. People were followed until development of IP/RA or censored at date of death or May 2014, whichever came first. Results: ACPA was measured in 18, 628 EPIC participants aged 40-79 years. ACPA was positive in 429 subjects (2.30%) of the whole EPIC population including 104 patients with prevalent IP/RA (35.6% ACPA positive, median titre 6.95 [IQR 3.75 – 121.2] U/ml) and 173 (16.8% ACPA positive, median titre 5.14 [IQR 3.37 – 9.41] U/ml) subjects who developed IP during 311, 051 person years of follow-up. Cross-sectionally, current and former smokers (OR 1.60, 95%CI 1.95 to 2.13 and OR 1.29 95%CI 1.02 to 1.55, respectively) and older age (OR 1.01 95%CI 1.00 to 1.03) were associated with ACPA positivity. Gender and socio-economic status were not associated with ACPA. Of 173 patients who developed IP and were notified to NOAR, 85 (49.4%) fulfilled the 2010 ACR/EULAR criteria for RA at entry to the NOAR cohort. ACPA status was predictive for the development of IP/RA (adjHR 10, 3 95%CI 6.90 to 15.34). The interaction between ACPA and smoking was not significant. Conclusions: ACPA was positive in 2.1% of a general population sample aged 40-79 years old. People who were ACPA positive were 10 times more likely to develop IP/RA in the next 3-10 years than those ACPA negative subjects. ACPA may be a useful adjunct to other screening approaches to identify people at higher risk of developing IP/RA. Disclosure of Interest: None declared